Monosaccharide coatings on nanoparticles affect protein corona formation but not the interaction with their binding receptor - Clemente, Eva; Mateu, Ruth; Ferreira, Avelino; Ludtke, Tanja; Lopez, Hender; Moya, Sergio E.; Lay, Luigi; Soliman, Mahmoud G.; Monopoli, Marco P. (Frontiers in Nanotechnology, 2025)
Surface coatings with polyethylene glycol (PEG) polymers have often been employed to improve nanoparticles (NPs) biocompatibility and extend circulation time by reducing protein adsorption. PEGylated NPs benefit from steric hindrance and repulsion effects, which are influenced by PEG molecular weight, density, and chain conformation. However, repetitive exposure to PEG can trigger acute and chronic immunological responses as a result of the development of Immunoglobulin G anti-PEG antibodies. NPs functionalisation with glycans has become an emerging approach to increase their biocompatibility as these biomolecules are highly hydrophilic, biocompatible, interact with biological receptors expressed in the body, and can be conjugated, controlling their orientation. In this study, we developed a series of gold NPs (AuNPs) coated with PEG linkers of different lengths and conjugated with mannose (Man) or sialic acid (Sia) glycans, and we carried out a detailed characterisation prior to and after exposure to biological fluids to study their behaviour and protein corona formation. Our findings show that the glycan-coated NPs exhibit stabilisation after protein interaction, with Man coatings showing the lowest protein affinity and that the glycans are biologically active and capable of binding to glycan receptors (such as Concanavalin A) despite the presence of a complex protein environment. Results indicate that glycan modification of PEGylated nanoparticles reduces nonspecific interactions while preserving active targeting properties, underscoring their potential for therapeutic applications.